InSilico Analysis and Homology Modeling of Tetrahydroprotoberberine Oxide involved in the Berberine Biosynthesis - Kanchan Kumari (Emerging Trends in Metabolites, 2024)
Objective: Berberine, a bioactive compound found in various plant species, exhibits diverse pharmacological properties with potential applications in pharmaceutical research. The biosynthesis of berberine involves several enzymatic steps, with (S)-tetrahydroprotoberberine oxidase playing a pivotal role. This study aimed to elucidate the structural and functional characteristics of (S)-tetrahydroprotoberberine oxidase to better understand its role in berberine biosynthesis and its potential biotechnological applications. Methods: Using bioinformatics tools and computational methods, the physicochemical properties, secondary structure, and molecular functions of the enzyme were analyzed. Predictions of solvent accessibility, transmembrane topology, and protein-protein interaction sites were made to gain insights into its structural organization and functional implications. Additionally, KEGG pathway analysis revealed the enzyme's involvement in metabolic pathways relevant to berberine biosynthesis and plant metabolism. Results: The results provided valuable insights into the (S)-tetrahydroprotoberberine oxidase enzyme, highlighting its potential as a target for biotechnological applications and pharmaceutical development. However, the study acknowledges the limitations inherent in computational predictions and emphasizes the need for experimental validation to confirm the findings. Conclusion: Overall, this research contributes to our understanding of (S)-tetrahydroprotoberberine oxidase and lays the groundwork for future studies aimed at exploring its biochemical properties and applications in various fields. Overall, this research contributes to our understanding of (S)-tetrahydroprotoberberine oxidase and lays the groundwork for future studies aimed at exploring its biochemical properties and applications in various fields. Future work should focus on experimental validation of the computational predictions, which will be crucial for harnessing the enzyme's full potential in pharmaceutical and biotechnological innovations
Keywords: (S)-tetrahydroprotoberberine oxidase; Berberine; Berberis wilsoniae; InSilico Analysis; THP Oxidase